Use of Natural Ingredients on the banks of the Lulut River as Self-medication and Potential for Pharmaceutical Product Development - Melviani Melviani; Noval Noval (Fakultas Kedokteran Universitas Lambung Mangkurat, 2025)
Since ancient times, the people of the Banjar Tribe of South Kalimantan have used medicinal plants as a treatment for all kinds of diseases. However, over time, the forest area has been used as shifting cultivation, rubber plantations and oil palm plantations. This has resulted in a decrease in the number of plants in the forest, including medicinal plants. Apart from that, minimal information about types of medicinal plants in the community can also reduce public awareness of the use of medicinal plants as herbal medicines. This has resulted in concerns about the loss of use of medicinal plants from the forest in the future. So it is necessary to encourage the community to increase the role of traditional medicine. The aim of this research is to determine the use of natural ingredients as medicine in riverbank communities as well as efforts to develop the potential of medicinal plant products in the community as pharmaceutical preparations. The research method uses an observational research design with a cross-sectional approach and cluster sampling technique. This research involved 100 respondents from Sungai Lulut, South Kalimantan. The majority of respondents were women (76%) from the Banjar tribe (98%). The use of natural ingredients as traditional medicine, such as soursop leaves, which are the most commonly used, are often boiled and drunk to treat cancer, fever and diarrhea. The majority of respondents chose trees as the type of natural material used, especially the leaves. Information about traditional medicine was mostly obtained from the surrounding environment, while knowledge about the contents of natural ingredients, storage methods, and taboos or use was not generally known to respondents. for the development of pharmaceutical preparations which are most preferred in the form of tablets, capsules and pills.